(3GJLGgGJ GdQCi GdYGe fMh OhQ GdbfhGJ GdaVGFjI ai ehGLgI GdCReGJ (B: s (3OQGSI eSMjI (B/ s - (3efi YfJQ eMeO dWai YHOGdeDefs; (3HQcGJ YHOGdYRjR eMeO (B: s ((3GdbGgQI (B: s (3efi YfJQ eMeO dWai YHOGdeDef (B: s, 2021)
(3gOaJ gPg GdOQGSI GdGgJeGe HeYQaI GdOhQ GdPi jecf Cf Jbhe Hg hSGFd GdEYdGe HTcd YGe h GdbfhGJ GdaVGFjI HTcd NGU ai ehGLgI GdCReGJ h GdbVGjG GdOGNdjI(B: (3h cjajI eYGdLJgG ai GdHQGeL GdMhGQjI ddMO ef BKGQgG GdSdHjI h EjLGO GdMdhd GdCfSH dehGLgJgG(B: (3h CjVG GdJYQa Edi JCKjQ Jdc GdeYGdLI ai JTcjd GJLGgGJ GdQCi GdYGe fMhgG(B. (3h bO Je JWHjb GdOQGSI GdejOGfjI Ydi YjfI YeOjI bhGe```gG (B(400 (3ea````QOI(B) (3e``f GdLeghQ GdeUQi GdPj```f JH`dZ CYe```GQge (B(18 (3SfI aCcKQ(B): (3a``i GdaJ``QI ef (B1/7/2019 (3Edi (B15/11/2019: (3ai YOI eMGaXGJ eUQjI eeKdI ddeLJeY GdeUQi(B. (3Cge GdfJGFL GdJWHjbjI GdJi Je GdJhUd EdjgG(B: (3SjWQI GdehVhYGJ h GdCWQ GdeQLYjI GdGbJUGOjI HhLg YGe Ydi GdCReGJ h GdbVGjG GdJi JfGhdJgG GdHQGeL GdMhGQjI eMd GdOQGSI dCfgG JYJHQ GdCge Ydi GdSGMI GdeUQjI MGdjG eeG jOd ai HYV GdCMjGf Ch jeKd EfYcGSG ddNW GdOGNdi ddOhdI h JYHjQG Yfg(B. (3LGAJ (B((3THcI bfhGJ Ce Hi Si(B) (3HTcd YGe h bfGI (B((3Ce Hi Si eUQ(B) (3HTcd NGU ai ebOeI GdbfhGJ GdJi JMXi HOQLI eTGgOI cHjQI LOkG ef LGfH CaQGO YjfI GdOQGSI JdGgG (B((3THcI bfhGJ Oi Ce Si(B) (3Ke (B((3THcI bfhGJ Si Hi Si(B): (3eeG jOd Ydi EQJaGY MLe GdeTGgOI GdcdjI ddLeghQ ddbfhGJ GdaVGFjI GdZjQ eUQjI h GdeUQjI ShGA GdMchejI Ch GdNGUI ddMUhd Ydi GdCNHGQ GdeJYdbI HCge eSJLOGJ GdbVGjG h GdCReGJ GdOGNdjI(B. (3GMJdGd HQfGeL (B"(3GdMcGjI(B" (3Ydi bfGI (B((3Ee Hi Si(B) (3eUQ GdeQJHI GdChdi cCge HQfGeL MhGQi ef hLgI fXQ CaQGO YjfI GdOQGSI(B. (3KHJ hLhO YdGbI OGdI EMUGFjkG Hjf GdKbI ai GdeYdheGJ GdJi JbOegG GdaVGFjGJ Yf GdCReGJ ef LgI h GdNUGFU GdOjehLQGajI (B((3GdfhY (B- (3GdYeQ (B- (3GdeSJhi GdJYdjei (B- (3GdeSJhi GdGLJeGYi(B/ (3GdGbJUGOi (B"(3GdONd (B: (3fhY GdScf(B") (3ddeHMhKjf ef LgI CNQi(B. (3KHJ hLhO YdGbI GQJHGWjI OGdI EMUGFjG Hjf JQJjH ChdhjGJ GdbVGjG h GdCReGJ GdOGNdjI eMd GdOQGSI HhSGFd GdGYdGe eLJeYI ef fGMjI(B: (3h JQJjH ChdhjGJ gPg GdbVGjG dOi GdeHMhKjf ef fGMjI CNQis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEYdGe (B- (3bSe GdEPGYI h GdJdjaRjhfs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GJLGgGJ GdQCi GdYGes; (3GdbfhGJ GdaVGFjIs; (3ehGLgI GdCReGJs